A Smart Home Design Based On Arduino - Novita Delima Siahaan; Beni Satria (Jurnal Scientia, 2024)
An Arduino-based smart home is the implementation of a smart system that controls various devices in the house such as lights, fans, doors, and others to increase comfort, security, and energy efficiency. Arduino acts as the brain of this system, receiving input from sensors and providing output to the controlled devices. The system can be accessed and controlled remotely via the internet with the Blynk app, allowing users to control their home even when they are not at home. In this design, sensors such as gas sensors, temperature sensors and humidity sensors are used to detect environmental conditions and occupant activities. Arduino uses information from these sensors to make automatic decisions, such as turning on the lights when it detects movement at night or sounding an alarm when there is an LPG gas leak, adjusting the room temperature as needed. Security is also a main focus in this design. Door and window sensors are installed to detect intrusions, and notifications can be sent to users via the Blynk app if there is suspicious activity. By using Arduino as the main platform, this smart home design can be easily customized and developed further according to user needs. From the research results it can be seen that the system has functioned as it should, in accordance with the initial design